2010
DOI: 10.1111/j.1582-4934.2009.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐culture with mesenchymal stromal cells increases proliferation and maintenance of haematopoietic progenitor cells

Abstract: Mesenchymal stromal cells (MSC) have been suggested to provide a suitable cellular environment for in vitro expansion of haematopoietic stem and progenitor cells (HPC) from umbilical cord blood. In this study, we have simultaneously analysed the cell division history and immunophenotypic differentiation of HPC by using cell division tracking with carboxyfluorescein diacetate N-succinimidyl ester (CFSE). Co-culture with MSC greatly enhanced proliferation of human HPC, especially of the more primitive CD34+CD38−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
117
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(128 citation statements)
references
References 74 publications
11
117
0
Order By: Relevance
“…[15][16][17][18][19] Furthermore, replicative senescence affects the ability of MSC to support hematopoieisis. 20 We observed that MSC cultured with adult pHPL ceased proliferation after fewer than 50 PD, whereas more than 60 PD were possible in FBS-driven cultures. 21 It remains unclear whether common senescence-associated gene expression changes are induced in MSC that have been isolated using different isolation and culture methods.…”
Section: Introductionmentioning
confidence: 85%
“…[15][16][17][18][19] Furthermore, replicative senescence affects the ability of MSC to support hematopoieisis. 20 We observed that MSC cultured with adult pHPL ceased proliferation after fewer than 50 PD, whereas more than 60 PD were possible in FBS-driven cultures. 21 It remains unclear whether common senescence-associated gene expression changes are induced in MSC that have been isolated using different isolation and culture methods.…”
Section: Introductionmentioning
confidence: 85%
“…[41][42][43] MSC senescence influences not only differentiation potential but also the support of hematopoiesis. 44 To date, knowledge regarding the role of MSC senescence in hematopoietic support is limited. In this study, other than the classic feature of cellular senescence, Dicer1-KD MSC showed a significantly reduced capacity to support CD34 + cells in LTC-IC assays.…”
Section: Discussionmentioning
confidence: 99%
“…75 These functional changes are accompanied by continuous changes in their gene expression profile 76 and DNA-methylation pattern. 77 Furthermore, miRNA expression profiles vary in the course of culture expansion 78,79 and these may contribute to the supportive hematopoiesis function of MSC.…”
Section: Mirnas In the Hematopoietic Stem Cell Nichementioning
confidence: 99%